Factors Associated With Adherence to Outpatient Follow-Up in Patients With Idiopathic Intracranial Hypertension (IIH) - Aziz, Rem; Shah, Asha; Moss, Heather E. (Frontiers in Ophthalmology, 2021)
Idiopathic intracranial hypertension (IIH) is a chronic condition characterized by raised intracranial pressure of undetectable origin, that causes morbidity due to debilitating headaches and vision loss. Continuity of outpatient care is important to monitor for permanent vision loss, manage symptoms and limit emergency care. The purpose of this retrospective study was to identify factors associated with neuro-ophthalmology follow-up appointment completion among patients with IIH at a US academic medical center in order to establish evidence-based interventions to improve adherence patterns. Included are 111 completed or no-show neuro-ophthalmology return outpatient appointments by 23 subjects with IIH. Generalized estimating equation models were used to assess association between appointment completion status and factors previously shown to be associated with appointment adherence. Appointments were more likely to be completed during the summer (p=0.08) and by subjects with headache symptoms (p=0.06). Completed and no-show appointments did not differ by subject demographic or insurance factors. Further studies are needed to identify risk factors for lack of appointment adherence by patients with IIH, particularly those amenable to intervention, in order to improve continuity of care for IIH.